Considerações sobre as raízes do realismo de Charles S. Peirce - Castro, Thiago Ferreira da Motta Gehrmann (2020)
The main object of this master dissertation is the realism of C.S Peirce in its different forms. It is true that Peirce, throughout his vast work, vehemently criticized philosophical nominalism. We can observe Peirce's quote to the nominalism of Abelard and João de Salisbury (CP 8.30), Descartes, Locke, Hume, Reid (CP 1.9), Berkley (8.26), Kant Leibniz, Wolf (6.590), Hegel (1.19) among others. On the other hand, Peirce joined an extreme scholastic realism, according to his own self-proclamation (CP 5.470). In another aspect, Peirce was notorious for being an expert logician, having made such a science advance from the contributions of G. Boole and A. De Morgan. However, it can only do so thanks to the scholastic doctors (CP 1.15) and their realism, since their doctrine of connaturality postulates that external facts are corrective factors for thought, including the logical one. Peirce even uses the chemical idea of valence, for logical predication (CP 5.469). From this radical realism, Peirce lays the foundations for the logic of the relative, the theory of probabilities and what we now know as truth tables. However, the author's realism has yet another facet. Combined with concepts such as his objective idealism, synechism, Peirce's realism becomes a realism in process, which points to a vector of crystallization in thirdness. Analogous to a symphony that, over time, spreads eidos and agape, the more the continuum travels, the more real and rational the cosmos becomes